International educational innovation and public sector entrepreneurship - Wiseman, Alexander W., 1968- (International perspectives on education and society ;, 2013)
The internationally comparative perspective of the volume will frame educational innovation and social entrepreneurship using both the globalization and contextualization of educational quality and opportunity in disadvantaged communities worldwide as a foundation. Through the use of both empirical research reports and case study examples, this volume will examine the contributions of social entrepreneurs through educational programs, projects and systems worldwide, and how the social, cultural and political communities in each nation contextualize educational innovations. Chapters will examine evidence to assess the impact of social entrepreneurship in education and to make recommendations for innovative educational change. This volume will also highlight the importance of theory in both understanding and guiding innovative ideas in every stage of entrepreneurial development from research-to-practice.